The Influence Of Intellectual Capital, Operating Capacity, And Operating Cash Flow On Financial Distress In Companies That Do Ipo In Indonesia In 2022 (Empirical Study In The Period 2022-2024) - Macadafi, Baris; Eka Putri, Zuwesty (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2026)
This study investigates the effect of intellectual capital, operating capacity, and operating cash flow on financial distress in companies listed on the IDX in 2022, with an observation period from 2022 to 2024. The analysis uses panel data regression on 129 companies, with financial distress measured by a modified Altman Z-score. The results show that intellectual capital and operating cash flow have a positive impact on financial distress, while operating capacity has a negative effect. This research adds a gap by incorporating intellectual capital as a factor affecting financial distress and focusing on empirical studies of companies listed in 2022. Intellectual capital is crucial for improving efficiency, innovation, and the resilience of human resources, as it plays a central role in organizational performance, as noted by Lee, Sukhumpong, et al. (2023), emphasizing the importance of human resource management in driving growth and competitiveness in the global market. These findings provide valuable insights for investors and management regarding the financial health of post-IPO companies in the Indonesian capital market.